Method of training pilots of the latest-generation aircraft to interact with crews of other aircraft - I. S. Muravyov (Научный вестник МГТУ ГА)
Training pilots of latest-generation aircraft to interact with other crews in flight is complicated by the high level of cockpit automation and information overload of crews, on the one hand, and by the responsibility of pilots for decisions made regarding air traffic, on the other hand. Since the unified methodology for training pilots to interact with other crews in the same airspace is not available, the development of qualitative training is required. To address this issue, a method, based on a preliminary calculation of the amount of information which is necessary to process by a pilot when training depending on the type of this information for the efficient formation of a conceptual model of air traffic in flight, has been developed. The method of forming a conceptual model of air traffic is based on the application of a mathematical model of “random walk with absorption”. The method consists of three phases. In the first flight phase, a pilot should operate a training flight en route. In the first flight of the second training phase, a trainee evaluates the tendency for the approach (separation) of the assessed aircraft to the trainee aircraft. In the second flight of the second phase, the assessed aircraft position is determined by the crew position and altitude reports, in the third flight – by the crew position, heading and altitude reports. In the third training phase, when operating three flights primarily en route, a trainee is supposed to evaluate the air situation according to all the parameters reported by crews operating in the same airspace. After flights of the second and third training phases, the pilot is meant to analyze and evaluate the air situation while operating a flight comprehensively by the number of aircraft in the flight area, their position and the sequence of their motion. The experimental results made it possible to determine that participants in the experimental group were 24% more efficient in evaluating the air situation and interacting with other crews in flight in the same flight area compared to the control group pilots. Processing of the experimental results showed that when employing the proposed training method, the reliability of the latest-generation aircraft crew interaction at the automatic piloting mode was statistically significantly increased.